Co-administration of isoprenaline and phenylephrine induced a new HFrEF mouse model through activation of both SNS and RAAS - Su, Huimin; Liu, Ming; Wang, Siteng; Tian, Beiduo; Hu, Hao; Ma, Li-Kun; Pan, Jianyuan (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe pathogenesis of human heart failure is diverse, and a large number of animal models have emerged to better understand the development of heart failure in humans. Among them, there are several methods of induction in mouse heart failure models, each with its advantages and disadvantages. The use of drug induced heart failure models has greatly facilitated basic research and reduced the disadvantages of time-consuming and labor-intensive surgical modeling.MethodsIn our experiments, we used a combination of isoprenaline (ISO) and phenylephrine (PE) for modeling; we aimed to evaluate whether it is superior to conventional drug-induced models, especially those induced by isoprenaline alone. The ISO and PE were administered for 2 weeks by subcutaneous implantation with a micro-osmolar pump, and the mice were monitored dynamically for cardiac ultrasound and blood pressure.ResultsRNA sequencing of myocardial tissues after execution of mice further clarified that hypertrophy, fibrosis genes, Sympathetic nervous system (SNS), and Renin-angiotensin-aldosterone system (RAAS) pathways were upregulated.DiscussionTherefore, we conclude that the ISO/PE-induced mouse heart failure model can activate both the SNS and RAAS, through the activation of both α-adrenergic receptor (α-AR) and β-adrenergic receptor (β-AR), which is more consistent with the development of human heart failure than the ISO-induced model and is expected to be a unique and representative heart failure modeling method.